2002
DOI: 10.1161/01.atv.0000014427.80594.8f
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Plasminogen Activator Inhibitor-1 in Endothelial Cells by Basic Fibroblast Growth Factor and Its Modulation by Fibric Acid

Abstract: Plasminogen activator inhibitor-1 (PAI-1) inhibits fibrinolysis and proteolysis. Basic fibroblast growth factor (bFGF) stimulates angiogenesis, which requires regional proteolysis. Because modulation of vasculopathy requires tight control of proteolysis, effects of bFGF on PAI-1 expression in endothelial cells (ECs) were characterized. bFGF increased PAI-1 mRNA and accumulation of PAI-1 protein in conditioned media in human umbilical vein ECs. The bFGF-mediated increase in PAI-1 mRNA was attenuated by inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 35 publications
4
34
0
1
Order By: Relevance
“…In the current study we observed an increase in F3 expression in the vessels of diabetic mice and have confirmed previous findings demonstrating the attenuation of F3 with fibrate treatment in endothelial cells [30], monocytes and macrophages [44].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the current study we observed an increase in F3 expression in the vessels of diabetic mice and have confirmed previous findings demonstrating the attenuation of F3 with fibrate treatment in endothelial cells [30], monocytes and macrophages [44].…”
Section: Discussionsupporting
confidence: 93%
“…Tissue factor has also been shown to be under the regulation of NF-κB [30] and be upregulated in diabetes, a state of increased thrombosis associated with plaque rupture [24]. In the current study we observed an increase in F3 expression in the vessels of diabetic mice and have confirmed previous findings demonstrating the attenuation of F3 with fibrate treatment in endothelial cells [30], monocytes and macrophages [44].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Also, FGFs modulate the expression of uPA receptor on the endothelial cell surface, thus allowing the localization of the proteolytic activity at the leading edge of the cell at the front of migration [22]. Furthermore, FGF1 and FGF2 induce the expression of the plasminogen activator inhibitor (PAI)-1 in cultured endothelial cells leading to a fine modulation of the proteolytic balance [23][24][25].…”
Section: Extracellular Matrix Degradationmentioning
confidence: 99%
“…Aside from the established role of Ets-1 in regulating the expression of MMP-1, -3 and -9 (Sementchenko and Watson, 2000), it also has been reported that plasminogen activator inhibitor-1 is a target gene for Ets-1 (Kaneko et al, 2002). Similarly, the TIMP-1 promoter is activated by Ets-1 (Logan et al, 1996).…”
Section: Introductionmentioning
confidence: 99%